Pengaruh Kualitas Aktiva Produktif, Capial Adequacy Ratio dan Ukuran Perusahaan Terhadap Profitabilitas pada Perusahaan Perbankan yang Terdaftar di BEI Tahun 2010-2014 - Ramadhanti, Fauziah; Kurniawati, Tri; Tasman, Abel (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2016)
The aim of study is to examine the effect of Earning Assets Quality measured by Bad Debt Ratio (BDR), Capital Adequacy measured by Capital Adequacy Ratio (CAR), and Firm Size measured by Ln (total asset) to Profitability in Banking Sector Companies listed on the Indonesia Stock Exchange. This study uses causative. The population in this study are all banking sector companies listed on the Indonesia Stock Exchange between 2010 and 2014.Â The sample is determined by purposive sampling to obtain 26 companies. Type of data using secondary data obtained from www.idx.co.id. The analytical method used is pool regression analysis. BasedÂ on the results of the study concluded that (1) Earning assets quality have significant negative effect on profitability (2) Capital adequacy have positive no significant effect on profitability, (3) Firm sized have negative no significant effect on profitability.